2021
DOI: 10.1136/bmjnph-2021-000280
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition content of summative examinations within an Australian 4-year graduate entry medical course: 2013–2016

Abstract: BackgroundPoor nutrition is a major contributor to chronic disease, but the level of nutrition education in medical training is limited. Deakin University Medical School has been working to embed more nutrition into the curriculum since 2009.AimTo assess the nutrition content of all summative examinations in the Bachelor of Medicine, Bachelor of Surgery over a 4-year period.MethodsThe type, amount and scope of nutrition-related questions were assessed in all summative examinations delivered to all 4-year level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
3
2
0
Order By: Relevance
“…In this context, the overall number of identified nutrition-related questions appears to be very low in our sample. Our findings are essentially in line with previous studies from the United States of America and Australia, although the number of total questions in our analysis seems to be slightly lower [21,22]. Perlstein et al assessed the nutrition content of the Bachelor of Medicine/Bachelor of Surgery curriculum at Deakin University Medical School in Australia between 2013 and 2016 [22].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In this context, the overall number of identified nutrition-related questions appears to be very low in our sample. Our findings are essentially in line with previous studies from the United States of America and Australia, although the number of total questions in our analysis seems to be slightly lower [21,22]. Perlstein et al assessed the nutrition content of the Bachelor of Medicine/Bachelor of Surgery curriculum at Deakin University Medical School in Australia between 2013 and 2016 [22].…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are essentially in line with previous studies from the United States of America and Australia, although the number of total questions in our analysis seems to be slightly lower [21,22]. Perlstein et al assessed the nutrition content of the Bachelor of Medicine/Bachelor of Surgery curriculum at Deakin University Medical School in Australia between 2013 and 2016 [22]. The authors reported that approximately 10% of the exam questions in the investigated medical course were nutrition-related.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The current study highlights that psychology professional associations may need to provide further CM relevant training for psychologists, given both a high level of psychologist engagement with CM and that 87% of surveyed psychologists perceive psychology as a field should provide more training on CM. Our findings relating to these specific issues have some similarities to the findings from studies of student doctors in Australia, where it was highlighted that nutrition education, for example, may not be sufficient to support nutrition related competencies in medical training and subsequently in their clinical practice [ 25 , 41 ]. Findings reported in previous literature, as well as those identified from the current study, highlights that psychologists perceive gaps in their knowledge about a number of CM approaches, including nutrition, and how to integrate them into practice [ 8 , 13 , 38 ].…”
Section: Discussionsupporting
confidence: 70%